Avoided ferromagnetic quantum critical point: Antiferromagnetic ground state in substituted CeFePO. Issue 1 (15th July 2016) - Jesche, A.; Ballé, T.; Kliemt, K.; Geibel, C.; Brando, M.; Krellner, C.
Abstract: We have investigated single crystals of two substitution series Ce(Ru1−x Fex )PO and CeFe(As1−y Py )O in the vicinity to the quantum critical material CeFePO by means of magnetic‐susceptibility and specific‐heat measurements. We observe an antiferromagnetic ground state in the vicinity of the quantum critical point, with pronounced metamagnetic transitions for H ∥ c, which is the magnetically hard direction. Our results verify that a ferromagnetic quantum critical point is avoided in substituted CeFePO, because we clearly demonstrate that the ferromagnetic ground state changes into an antiferromagnetic one, when approaching the quantum critical point. Temperature–substitution phase diagram of the series Ce(Ru1−x Fex )PO and CeFe(As1−y Py )O.